2022
DOI: 10.3390/vaccines10111834
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Vaccination of the Population of Romania against Monkeypox in Terms of Medical Security

Abstract: Although it has been shown in numerous studies that immunization of the population by vaccination is the most effective way to protect against smallpox or other polioviruses, the anti-vaccination public rhetoric recorded during the COVID-19 pandemic is likely to influence the populations acceptance of vaccination against newly emerging viruses. This fact influenced our decision to study the vaccination of the Romanian population against the virus that causes monkeypox, aiming to identify the degree of complian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…In this way, the level of worry varied among different studies. This level varied from 26.37% of the total population [ 29 ] and 28.5% among French and Belgian healthcare professionals [ 23 ] to 60.4% among the general population in Saudi Arabia [ 15 ]. Moreover, 37.5% of the studied Saudi healthcare workers were more concerned about MPOX than about COVID-19 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, the level of worry varied among different studies. This level varied from 26.37% of the total population [ 29 ] and 28.5% among French and Belgian healthcare professionals [ 23 ] to 60.4% among the general population in Saudi Arabia [ 15 ]. Moreover, 37.5% of the studied Saudi healthcare workers were more concerned about MPOX than about COVID-19 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained from the different studies showed that the lowest vaccination acceptance rate was obtained in the general population in Romania 29% [ 29 ], while the highest rate was obtained among healthcare professionals in China (90.1%) [ 25 ] ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the willingness rate of Mpox vaccination varied among different populations and regions [ 43 ]. In the general population, the willingness rate to get the Mpox vaccine ranged from 29% in Romania to 50.6% in Saudi Arabia [ 25 , 44 ]. Among healthcare workers, the rate of willingness to get the Mpox vaccine varied from 8.8% in the Czech Republic to 90.1% in China [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%